2015
DOI: 10.3766/jaaa.26.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Comparing NAL-NL1 and DSL v5 in Hearing Aids Fit to Children with Severe or Profound Hearing Loss: Goodness of Fit-to-Targets, Impacts on Predicted Loudness and Speech Intelligibility

Abstract: Although targets between 0.25 and 2 kHz were well matched for both prescriptions in commercial hearing aids, gain targets at 4 kHz were matched for NAL-NL1 only. Although the two prescriptions differ markedly in estimated loudness, they resulted in comparable predicted speech intelligibility for medium and high input levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…This was due to the limitations of the hearing aid itself (Ching et al, 2010;McCreery et al, 2013;Quar et al, 2013). After comparing the fit-to-targets achieved by a commercial hearing aid among children with moderately severe to profound hearing losses, Ching et al (2015) reported that although targets between 250 and 2000 Hz were well matched for both NAL-NL1 and DSL v5 prescriptions, gain at 4000 Hz were matched for NAL-NL1 only. This is because the DSL v5 Child procedure normally prescribes higher overall gain, especially for high-frequency region (Ching et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This was due to the limitations of the hearing aid itself (Ching et al, 2010;McCreery et al, 2013;Quar et al, 2013). After comparing the fit-to-targets achieved by a commercial hearing aid among children with moderately severe to profound hearing losses, Ching et al (2015) reported that although targets between 250 and 2000 Hz were well matched for both NAL-NL1 and DSL v5 prescriptions, gain at 4000 Hz were matched for NAL-NL1 only. This is because the DSL v5 Child procedure normally prescribes higher overall gain, especially for high-frequency region (Ching et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The HLD refers to the decreased ability of the damaged cochlea to extract information even when it is audible (Ching et al, 1998;. Ching et al (2015) reported that on average, the SII was lower for NAL-NL1 than for DSL v5 prescription at low input level. Lower SII and possible better fit-to-targets achieved by NAL-NL1 procedure may affect the conclusions made in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, audiologists continue to fit HAs for this population. Advances in digital HA technology and use of evidence-based best practices for HA fitting now enable close approximations to prescription targets in cases of S/PHL (Keidser et al, 2008;Quar et al, 2013;Ching et al, 2015), although a given listener's preferences along with the severity of the hearing loss can increase the difficulty of the fit for these listeners (Keidser et al, 2007).…”
mentioning
confidence: 99%